Persepsi Pegawai Kantor Desa terhadap Penggunaan Jasa Bank Syariah: - Iqbal Aji Arianto; Sri Sudiartri (VISA: Journal of Vision and Ideas, 2022)
The goal of this study was to discover why employees of the Laut Dendang village office choose to use the services of a sharia bank, and what factors influence their knowledge and attitudes. Field research using a qualitative approach is what this type of study is called. Employees at the Laut Dendang village office served as data sources for this study. Data collection is done by observation, interviews, and documentation, while data processing and analysis procedures are done in four stages: data reduction, data presentation, conclusion drafting, and data validity verification. The study's findings revealed that employees at the Laut Dendang village office have a positive attitude toward using Islamic banks, as evidenced by the employees' knowledge that Islamic banks are free of usury and that Islamic banks have contracts and profit sharing systems, making them less burdensome and harmful to those who have made the contract. Employees benefit from Islamic banks' knowledge and attitude toward their services, as well as cheaper administrative costs. Employees at the Laut Dendang village office primarily use traditional banking services as long-term savings. Keywords: Perception, Employees, Islamic Bank